Stability Analysis Of Two-Position Control System In Interacting Tanks Using Describing Function Method - Andi, Purwandito Tulus Asmoro (Fidelity : Jurnal Teknik Elektro, 2024)
In a water storage unit consisting of 3 interacting tanks, in its operation there will be problems if manual control is used, because if manual control is not optimal, then when filling water in the three tanks it will cause water overflow, which results in a lot of water being wasted. Two-position control, or "on-off," is a control system that is suitable for use in regulating the water level in the storage unit tank. In a two-position control system, if the frequency of water up and down (Limit Cycle) is large, it will cause an increase in the number of "switching" and "on-off" operations of the switch and solenoid valve per minute, so that the system becomes unstable and will shorten the life of the component. The Describing Function (DF) method is an analysis method that can determine the Limit Cycle frequency based on the width of the water up and down range (hysteresis) of the two-position control system, with the aim of determining the hysteresis parameters that cause the system to be stable.